Patterns and predictors of therapeutic response to efgartigimod in acetylcholine receptor-antibody generalized myasthenia gravis subtypes - Jin, Lei; Zou, Zhangyu; Wang, Qinzhou; Zeng, Wenshuang; Jiang, Qilong; Chen, Jing; Shi, Jianquan; Yu, Yanyan; Hong, Daojun; Zeng, Quantao; Tan, Song; Yue, Yaoxian; et al. (Therapeutic advances in neurological disorders, 2025)
Plain language summary Patterns and predictors of therapeutic response to efgartigimod in AChR generalized myasthenia gravis Myasthenia Gravis (MG) is an autoimmune disorder that can lead to potentially life-threatening complications. Efgartigimod is an approved biologic for generalized myasthenia gravis (gMG). However, the patterns and predictors of therapeutic response to efgartigimod among the acetylcholine receptor-generalized MG (AChR-gMG) subtypes remain inconclusive. Our findings revealed patterns of treatment responses among AChR-gMG subtypes, with LOMG patients potentially presenting a more sustained response.